Ideology, family policy and gender economic inequality: Different models, different tradeoffs - Hadas Mandel (Luxembourg Income Study (LIS), 2007)
This paper focuses on cross-national differences in patterns of gender economic inequality, revealing their affinity to both welfare state policies and prevailing conceptions of gender equality. By mapping multiple aspects of inequality and assembling them into distinctive profiles, the paper shows that each pattern of state intervention is accompanied by an uneven record of achievements and failures in promoting gender equality. These tradeoffs can best be understood by placing them in the ideological contexts in which gender-related policies are embedded. Empirical illustrations are provided for four countries - Sweden, the USA, Germany and Italy - in each of which both the welfare state and the pattern of gender stratification are qualitatively distinct. Data are presented on labor force participation, women's placement in the occupational and wage hierarchies, their economic wellbeing, and their autonomy from male partners.
Keywords: 330; Geschlechterdiskriminierung; Gleichberechtigung; Ideologie; Familienpolitik; Schweden; USA; Deutschland; Italien